RNA N6-Methyladenine Modification, Cellular Reprogramming, and Cancer Stemness - Chen, Huarong; Wang, Yifei; Su, Hao; Zhang, Xiaoting; Chen, Hongyan; Yu, Jun (Frontiers in Cell and Developmental Biology, 2022)
N6-Methyladenosine (m6A) is the most abundant modification on eukaryote messenger RNA and plays a key role in posttranscriptional regulation of RNA metabolism including splicing, intracellular transport, degradation, and translation. M6A is dynamically regulated by methyltransferases (writers), RNA binding proteins (readers), and demethylases (erasers). Recent studies demonstrate that perturbation of m6A regulators remarkably influences cell fate transitions through rewiring various biological processes such as growth, differentiation, and survival. Moreover, aberrant m6A modification is implicated in a variety of diseases, in particular cancer. In this review, we describe the functional linkage of m6A modifications to cellular reprogramming and cancer stemness properties.